Komunikasi dengan Roh Leluhur sebagai Tradisi Spritual di Indonesia dan Refleksinya bagi Iman Kristen (International Forum of Researchers and Lecturers, 2025)
The tradition of communicating with ancestral spirits remains a spiritual practice upheld by various indigenous communities in Indonesia. This tradition is considered a form of respect toward ancestors who are believed to maintain a spiritual connection with their descendants. This article aims to trace the historical roots and cultural meanings of communication with ancestral spirits and reflect on its implications for the Christian faith. Using a qualitative approach and literature review of spiritual practices among several ethnic groups, it was found that such communication is often rooted in relational values, reverence, and the search for life’s meaning. However, Christian reflection calls believers to distinguish between cultural honor and beliefs that may contradict faith in the living God. This article offers a dialogical and contextual approach to wisely and theologically understand and respond to this phenomenon.